Deferoxamine but Not Dimethyloxalylglycine, L-Mimosine, or Cobalt Dichloride Can Interfere with the MTT Assay. (18th November 2018) - Müller, Anna Sonja; Janjić, Klara; Oberoi, Gunpreet; Pensch, Manuela; Kurzmann, Christoph; Moritz, Andreas; Agis, Hermann
Abstract : Hypoxia mimetic agents (HMAs) have been shown to have a positive influence on cellular functions in a multitude of tissue regenerative strategies. Novel experimental approaches use biomaterials as carriers for controlled delivery of these HMAs. Here, the cytotoxic aspects of biocompatibility are of key relevance. The MTT assay is widely used to evaluate cytotoxicity and proliferation. Based on the implications from the proceeding research we hypothesized that specific HMAs such as deferoxamine at high concentrations can interfere with the MTT assay. Thus, the aim of this study was to test the repercussions of the HMAs dimethyloxalylglycine, deferoxamine, L-mimosine, and CoCl2 on the validity of the MTT assay. Murine MC3T3-E1 cells were cultured in serum-free alphaMEM and in alphaMEM supplemented with 10 % fetal bovine serum with the HMAs dimethyloxalylglycine, deferoxamine, L-mimosine, and CoCl2, respectively, at 3 mM-0.3 mM for 24 h (experimental groups). Cells without HMAs served as control (control groups). The same experiments were performed with medium and phosphate buffered saline (PBS) without cells. In all settings MTT solution was added to PBS-washed or unwashed culture plates for the last two hours of the incubation period. Then MTT solution was removed and dimethyl sulfoxide was added to dissolve the formazan crystals and absorption was measured. Our data show that the presence of deferoxamine can interfere with the MTT assay if not removed before the addition of MTT. This is particularly important when evaluating cell viability in setups where deferoxamine-loaded biomaterials are used.